Parental Warmth and Hostility and Child Executive Function Problems: A Longitudinal Study of Chinese Families - Lam, Chun Bun; Chung, Kevin Kien Hoa; Li, Xiaomin (Frontiers in Psychology, 2018)
This study examined the longitudinal associations of maternal and paternal warmth and hostility with child executive function problems. Data were collected for two consecutive years from 333 kindergarten children who resided in Hong Kong, China, as well as their mothers, fathers, and class teachers. At Time 1, the average age of children was 57.73 months, and 56% of them were girls. At Time 1, mothers and fathers rated their own parenting practices with their children. At Times 1 and 2, class teachers rated children’s problems in three aspects of executive functions, including updating/working memory, inhibition, and shifting/cognitive flexibility. As control variables, at Time 1, parents provided information on child and family demographic factors, and children completed verbal ability tasks. Multilevel modelling revealed that, controlling for child and family demographic factors, child verbal abilities, and paternal parenting practices, maternal hostility, but not maternal warmth, was linked to increases in child inhibition and shifting/cognitive flexibility problems. Moreover, paternal hostility, but not paternal warmth, was linked to increases in updating/working memory problems. Theoretically, this study highlighted the importance of considering the contributions of both mothers and fathers, and differentiating between positive and negative aspects of parenting, when examining the development of child executive functions. Practically, this study pointed to the utility of targeting maternal and paternal hostility in family intervention and community education in order to reduce child executive function problems.